(+)-Pentazocine attenuates SH-SY5Y cell death, oxidative stress and microglial migration induced by conditioned medium from activated microglia. (6th March 2017) - Heiss, Kathrin; Raffaele, Marco; Vanella, Luca; Murabito, Paolo; Prezzavento, Orazio; Marrazzo, Agostino; Aricò, Giuseppina; Castracani, Carlo Castruccio; Barbagallo, Ignazio; Zappalà, Agata; Avola, Roberto; Li Volti, Giovanni
Highlights: (+)-Pentazocin, a σ1 agonist, inhibits microglial cell migration. (+)-Pentazocin protects SH-SY5Y cells from microglia activation. (+)-Pentazocin prevents oxidative stress and neuroinflammation following microglial activation. Abstract: Background: Sigma receptors (σ1 R) are expressed both in neurons and microglia and can be considered as a promising target for developing pharmacological strategies for neuroprotection in various experimental models. The aim of the present study was to test the effect of (+)-pentazocine, a putative σ1 R agonist, in an in vitro model of neuron/microglia crosstalk following hypoxia/reoxygenation. Methods: Microglia (BV2 cells) was exposed (3 h) to 1% oxygen and reoxygenation was allowed for 24 h. Conditioned media obtained from this experimental condition was used to treat neuroblast-like cell line (SH-SY5Y cells) in the presence or absence of (+)-pentazocine (25 μM). Cell viability was measured by cytofluorimetric analysis, whereas inflammation and oxidative stress were evaluated by the expression of Hsp70, GAD, SOD and p65. Microglial cell migration was also evaluated by Xcelligence technology. Results: Our results showed that (+)-pentazocine was able to increase SH-SY5Y cell viability following exposure to microglial-conditioned medium. Furthermore, (+)-pentazocine was also able to inhibit microglial cell toward neuron treated with hypoxic conditioned medium. Finally, pharmacological treatment reduced the expression of inflammatory and oxidative stress markers (GAD, SOD and p65). Interestingly, hypoxic medium was able to reduce the expression of Hsp70 and such effect was prevented by (+)-pentazocine treatment. Conclusions: (+)-Pentazocine exhibits significant neuroprotective effects in our in vitro model of SH-SY5Y/microglial crosstalk thus suggesting that σ1 R may represent a possible strategy for neuroprotection.